HAKIKAT DEMOKRASI MENURUT MUHAMMAD HATTA: RELEVANSINYA DENGAN PENGEMBANGAN OTONOMI DAERAH - , Drs.Mat Jalil, M.Hum, Prof. Dr. Lasiyo.MA.MM ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The dissertation is entitled The Nature of Democracy According to Muhammad Hatta: The Relevance to the Development of Regional Autonomy. The theme is important to support the democratization process to strengthen the decentralization in Indonesia. The dissertation is intended to critically investigate the thought key concepts of Muhammad Hatta, to find out systematic and coherence explanation as a thought through political philosophy. The objective of the dissertation is to find out, give inventory and critically interpret systematic democracy concept of Muhammad Hatta, describe and analyze the autonomous region concepts, express and reflect Muhammad Hattaâs nature of democracy relevance to the development of regional autonomy. Material object of the dissertation is the nature of democracy according to Muhammad Hatta, while the formal object is political philosophy. This is a kind of literature research. The research data analysis is done by using qualitative research methods in philosophy aspects which is included historical method, description, internal coherence, and hermeneutic. The result shows that the nature of democracy is peopleâs sovereignity constructed from the ground up on the basis of collectivism peopleâs democracy which are realized through share work, imbued by Pancasila, and executed based on the truth, justice, honesty, kindness, brotherhood, and humanity. Democracy is a representation though discussion to urban level meetings as mediator and relevant implementation of regional autonomy to Muhammad Hattaâs spirit of democracy, where in the spirit of share work and empowerment of people with a political, religion, ethnic or tribal groups background in the nation's development planning and decision-making, can encourage equitable resource allocation and investment by the Government. Regional autonomy can empower people and create the regional independence. People handle the right and authority to determine the needs of their regional development. People get actively involved in the development and control the operation of local governance.